Manajemen Pembelajaran Pendidikan Agama Islam Berbasis Inklusi bagi Anak Disabilitas di Kota Makassar - Rd. Zaky Miftahul Fasa (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
Inclusive education, especially in the Islamic education (PAI) subject, is a guaranteed concept for citizens to get their right for education without exception. This study aims to determine how inclusion-based PAI learning management for children with disabilities in Makassar City uses qualitative methods and uses observation, interview and documentation study techniques. There are four findings in this study, namely: (1) learning planning has been prepared by Islamic Education teachers based on the curriculum of 2013 and adapted to the characteristics of the child and documented in the form of a syllabus and learning implementation plan, (2) the implementation of PAI teaching and learning activities are implemented with a strategy diverse learning; selecting and using varied learning methods; as well as the use of learning media, (3) evaluation of Islamic Education learning outcomes for children with disabilities is carried out by using test and non-test techniques, (4) there are obstacles in learning Islamic Education with children with disabilities, namely the competence of Islamic Education teachers in presenting the learning process, supporting facilities and the lack of handbooks (textbooks) for PAI for children with disabilities so that Islamic education learning is not optimal.